A Desire Seeks Its Dwelling : Gendering Literature Teaching from the Contributions of Feminist Pedagogies - Sardi, Valeria (International research in children's literature.)
In this article I set about theorising the construction of a gendered didactic of literature, one that accounts for alternative ways of reading and approaching literary texts in school settings. Throughout my article, I intend to trouble literary reading practices insofar as they are socio-cultural, embodied, and sexed-and-gendered in nature. To do so, I will borrow from literature teaching experiences set in high schools1 from the Buenos Aires province (Argentina). My writing will analyse pedagogical accounts of classroom happenings from the theoretical contributions of language and literature teaching, as well as from feminist, queer, and decolonial epistemologies and pedagogies. These theoretical approaches propose grappling with literature from local and embodied stances -against the grain of a colonial, capitalist, white, androcentric, encyclopaedistic, and hetero-cisnormative matrix -and, from that locus, seek to produce insights about alternative ways of conceptualising knowledge, pedagogical relationships, and the very subjects engaged in teaching and learning in pedagogical settings.